On the Perception of Monumental and Decorative Sculpture of St. Petersburg as an Object of Restoration in the 19th-21st Centuries (by the Example of the Sculptural Ensemble of the Mining Institute) - Schedrova, Olga V. (Actual Problems of Theory and History of Art, 2018)
The paper explores the history of the sculptural groups “Hercules and Antaeus” and “Rape of Proserpine by Pluto” from the portico of the Mining Institute and examines them as a fine example of repairing techniques applied to the stone sculpture in the 19th century. The sculptors, S. S. Pimenov and V. I .Demuth-Malinovsky, created the sculptural groups in 1809-1811. These groups are among the splendid examples of an architectural ensemble in which architecture and sculpture are interacting, complementing, and emphasizing the advantages of each other. The paper explores the history of the sculptural groups “Hercules and Antaeus” and “Rape of Proserpine by Pluto” from the portico of the Mining Institute and examines them as a fine example of repairing techniques applied to the stone sculpture in the 19th century. The sculptors, S. S. Pimenov and V. I .Demuth-Malinovsky, created the sculptural groups in 1809-1811. These groups are among the splendid examples of an architectural ensemble in which architecture and sculpture are interacting, complementing, and emphasizing the advantages of each other. The sculptural groups were never restored as an independent work of art. They were regarded as an integral part of the architectural ensemble ignoring specific methods suitable for decorative monumental sculpture. Pudostskiy limestone structure does not allow grinding and polishing the surface like marble. However, even such durable material is exposed to active destruction caused by changeable weather conditions, high humidity, and air pollution. At the end of the 19th century, during repair works in the building, the facade sculptures were painted in dark color to imitate bronze. At the same time, there was a question of the reconstruction of the sculptures in bronze. To create bronze copies, the special molds were made. The bronze copies were shown at the Exhibition of Fine Arts in Rome, in 1912. Emergency restoration works were carried out after the Second World War. Recent restoration works (2015) opened new pages in the history of the monument. The groups represent a typical example of restoration actions during previous years. The aims and methods of the restoration to be applied to these monuments reflect the most typical principles of the perception and interpretation of works in different historical periods.
Keywords: sculpture; restoration; ensemble; Mining Institute in Saint Petersburg; limestone; copies of sculpture; conservation; heritage